2021
DOI: 10.1002/mar.21581
|View full text |Cite
|
Sign up to set email alerts
|

It is different than what I saw online: Negative effects of webrooming on purchase intentions

Abstract: Webrooming is a two‐stage shopping process that begins with examining product options online followed by making a purchase at an offline store. In four experiments, we investigate webrooming effects on product evaluation and purchase intentions. The results suggest that webrooming (vs. non‐webrooming) has negative impacts on (1) perceived product performance vis‐à‐vis expectations and (2) purchase intentions for the products offline. Our moderated‐mediation analyses show that webrooming leads to lower perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Our results suggest that for items where product touch can be diagnostic (e.g., clothing, etc. ), not having an opportunity to touch products under consideration can attenuate the positive outcomes typically associated with product touch, potentially depressing sales revenues (i.e., Chung et al, 2022). Therefore, it may be advantageous for online retailers to offer “smaller” assortments for products where touch can be diagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that for items where product touch can be diagnostic (e.g., clothing, etc. ), not having an opportunity to touch products under consideration can attenuate the positive outcomes typically associated with product touch, potentially depressing sales revenues (i.e., Chung et al, 2022). Therefore, it may be advantageous for online retailers to offer “smaller” assortments for products where touch can be diagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…The latest research has started to explore the experience and outcomes of webrooming. For instance, Chung et al. (2022) found that webrooming can widen the gap between expectations and product performance, which eventually lowers purchase intentions.…”
Section: Literature Review and Conceptual Developmentmentioning
confidence: 99%
“…However, there is a limited understanding of factors and mechanisms driving consumers' webrooming behaviour, particularly in the digital marketing environment. To this end, we adopt the online–offline channel perspective (Chung et al. , 2022) to examine the role of online reviews (Arora et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, bricks and clicks businesses are designed to provide product-related information in webrooming for providing better opportunities to the consumers (Arora & Sahney, 2017, 2019Aw, 2019Aw, , 2020Choi & Yang, 2016;Flavián et al, 2016;Manss et al, 2020). In this way, Australian customers are always concerned about getting information from webrooming before purchasing the products for their satisfaction (Arora & Sahney, 2018, 2019Chung et al, 2022;.…”
Section: Consumer Behavior and Webroomingmentioning
confidence: 99%